CPA Review: Theory, Practice, Auditing/CPA Review: Problems and Solutions. - Parkinson, Paul W. (The Accounting Review, 1978)
Abstract Reviews the books "CPA Review: Theory, Practice, Auditing," and "CPA Review: Problems and Solutions," by David F. Fetyko and Elwyn L. Christensen.